89.7k views
16 votes
How do you solve 13 + 3 - 8x + 6 = 1 - 5x I dont get it

User Pierpy
by
5.3k points

2 Answers

11 votes

Answer: x=7

Step-by-step explanation: :)

User Teyzer
by
5.3k points
7 votes

Answer:

x = 7

Explanation:

How to solve your question

Your question is 13 + 3 − 8x + 6 = 1 − 5x

13 +3 - 8x + 6 = 1 - 5x

13 + 3 − 8x + 6 = 1 − 5x

Solve

Add the numbers

13 + 3 − 8x + 6 = 1 − 5x

22 − 8x = 1 − 5x

Rearrange terms

22 − 8x = 1 − 5x

−8x + 22 = 1 − 5x

Subtract 22 from both sides of the equation

−8x + 22 −22 = −5x + 1 − 22

Simplify

Subtract the numbers

−8x = -5x + 1 -22

-8x = -5x -21

Add 5x to both sides of the equation

-8x + 5x = -5x -21 + 5x

Simplify

Combine like terms

-3x = -21

Divide both sides of the equation by the same term

(-3x)/3 = (-21)/3

Simplify

Cancel terms that are in both the numerator and denominator

x = (-21)/(-3)

Divide the numbers

x = 7

User Vectorizer
by
4.9k points